Pemanfaatan Data Mining Dalam Menentukan Strategi Marketing Penerimaan Mahasiswa Baru - Alam (E-Jurnal Universitas Samudra, 2024)
This study aims to map patterns and find invisible information from new student admissions data by utilizing data mining technology. This research succeeded in mapping the pattern of prospective new students which is useful for determining the right marketing strategy according to the cluster. In order to achieve the research objectives, this research uses the K-Means Clustering algorithm and the Agglomerative Hierarchical Clustering algorithm. The data used in this study is Cipasung Tasikmalaya University's new student enrollment data from 2021 to 2023. The results of this study, the best clusters that were successfully formed were 5 clusters with the best K-Means Clustering algorithm. This research was also able to map some information based on the model formed.